Virtual-Reality Distraction and Cold-Pressor Pain Tolerance: Does Avatar Point of View Matter? - Dahlquist, Lynnda M. (Mary Ann Liebert, Inc., 2010)
This study tested the effects of distraction using virtual-reality (VR) technology on acute pain tolerance in young adults. Forty-one undergraduate students, aged 18–23 years, used a VR head-mounted display helmet, steering wheel, and foot pedal to play an auto racing video game while undergoing exposure to very cold water (cold pressor set at 1°C). Two different game views were tested that were hypothesized to affect the degree to which participants felt “present” in the virtual environment: a first-person view, in which the participant saw the virtual environment through the eyes of the game character being manipulated; and a third-person view, in which the participant viewed the game character from a distance. The length of time participants tolerated the cold-water exposure (pain tolerance) under each distraction condition was compared to a baseline (no distraction) trial. Subjects also rated the degree to which they felt “present” in the virtual environment after each distraction trial. Results demonstrated that participants had significantly higher pain tolerance during both VR-distraction conditions relative to baseline (no distraction) trials. Although participants reported a greater sense of presence during the first-person condition than the third-person condition, pain-tolerance scores associated with the two distraction conditions did not differ. The types of VR applications in which presence may be more or less important are discussed.